The Effect of Halofenate or Halofenate Free Acid on Human, Rat and Guinea Pig Platelet Aggregation - Minsker, D.H; Jordan, P.T; Kling, P; MacMillan, A; Hucker, H.B; Tocco, D.J (Thrombosis and Haemostasis, 1976)
Halofenate free acid (HFA), the major metabolite of the hypolipemic agent halofenate, blocked the secondary phase of human platelet aggregation induced by ADP, epinephrine, or thrombin; higher concentrations of clohbrate free acid (CFA) were required to produce similar inhibitory effects on platelet aggregation. HFA and CFA inhibited collagen-induced aggregation of human, rat, or guinea pig platelets. Halofenate orally administered to rats caused inhibition of collagen-induced aggregation when plasma levels of HFA exceeded 300 μg/ml, a clinically achievable human plasma concentration. The platelet inhibitory effects of clofibrate administration were less than those observed with halofenate administration.